Hemophagocytic syndrome and herpes virus infections - V. A. Anokhin; G. R. Fatkullina; L. B Akchurina (Журнал инфектологии, 2014)
Infection-associated hemophagocytic syndrome is a life-threatening condition characterized by prolonged fever, hepatosplenomegaly, and cytopenia—most commonly, thrombocytopenia and anemia. It is characterized by proliferation and activation of benign histiocytes, causing dysfunction of various organs. Herein, we report about two clinical cases of hemophagocytic syndrome, associated with cytomegalovirus and Epstein – Barr virus.